1997
DOI: 10.1083/jcb.136.4.845
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-associated Protein 2c Reorganizes Both Microtubules and Microfilaments into Distinct Cytological Structures in an Actin-binding Protein-280–deficient Melanoma Cell Line

Abstract: The emergence of processes from cells often involves interactions between microtubules and microfilaments. Interactions between these two cytoskeletal systems are particularly apparent in neuronal growth cones. The juvenile isoform of the neuronal microtubule-associated protein 2 (MAP2c) is present in growth cones, where we hypothesize it mediates interactions between microfilaments and microtubules. To approach this problem in vivo, we used the human melanoma cell, M2, which lacks actin-binding protein-280 (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
63
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 65 publications
5
63
0
Order By: Relevance
“…MAP2 proteins also determine the spacing between microtubules [Chen et al, 1992;Cunningham et al, 1997;Belanger et al, 2002]. MAP2b and MAP2c induce a spacing between microtubules of 60 nm and 20 nm, respectively.…”
Section: Stabilization and Organization Of Microtubules By Map2 Isoformsmentioning
confidence: 99%
See 1 more Smart Citation
“…MAP2 proteins also determine the spacing between microtubules [Chen et al, 1992;Cunningham et al, 1997;Belanger et al, 2002]. MAP2b and MAP2c induce a spacing between microtubules of 60 nm and 20 nm, respectively.…”
Section: Stabilization and Organization Of Microtubules By Map2 Isoformsmentioning
confidence: 99%
“…MAP2b and MAP2c induce a spacing between microtubules of 60 nm and 20 nm, respectively. Several studies indicated that the length of the projection domain was the main determinant of the spacing between microtubules [Chen et al, 1992;Cunningham et al, 1997;Belanger et al, 2002]. To further investigate this point, we generated truncated forms of MAP2b deleted from different portions of the projection domain and expressed them in Sf9 cells to measure their effects on microtubule spacing [Belanger et al, 2002].…”
Section: Stabilization and Organization Of Microtubules By Map2 Isoformsmentioning
confidence: 99%
“…Thus, the stabilization of microtubules does not seem to be the sole function of MAP2 in dendritic outgrowth. In recent years, our work and that of others (23)(24)(25)(26)(27)(28)(29) showed that MAP2 could also interact with actin microfilaments and neurofilaments. Thus, MAP2 could act as a cytoskeletal integrator in dendrites by linking together the three cytoskeletal elements.…”
mentioning
confidence: 99%
“…Besides microtubules, several additional proteins have been reported to interact with MAP2 in vitro, the best characterized of which is the type II regulatory subunit of PKA (32)(33)(34). Other proteins include F-actin (35)(36)(37)(38), calmodulin (39), and the mitochondrial outer membrane protein porin (40). The precise binding sites on MAP2 for these proteins have yet to be identified.…”
mentioning
confidence: 99%